(untitled) (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
Scientific research dedicated to shaping and educating the consciousness, worldview, and thinking of the younger generation on the basis of enlightenment emphasizes the effective use of the educational ideas of great scholars who made invaluable contributions to the development of world science. In the process of acquiring knowledge, expanding worldview and intellectual potential plays a practical and decisive role, and is regarded as a key pedagogical factor that determines the future.